Quadriceps and Hamstrings Activation Peaks Earlier as Athletes Repeatedly Hop, but There are Differences Depending on ACL Reconstruction Technique. - Einar Einarsson; Olivia Barbosa; Magnus Kjartan Gislason; Kristin Briem; Argyro Kotsifaki; Rodney Whiteley (International Journal of Sports Physical Therapy)
# Background